2007
DOI: 10.1111/j.1467-8683.2007.00557.x
|View full text |Cite
|
Sign up to set email alerts
|

Outside Directors, Ownership Structure and Firm Profitability in Korea

Abstract: The contribution of outside directors to firm performance has been shown to be inconsistent. Korean companies first began in 1998 to introduce outside directors to carry out governance reform. This paper analyses the impact of outside directors on corporate performance during the governance reform movement undertaken in Korea in 1999 as well as the moderating effect of the large shareholder and managerial ownership rate. We hypothesised a positive relationship between outside director effectiveness (outside di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
114
3
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(140 citation statements)
references
References 57 publications
(63 reference statements)
14
114
3
6
Order By: Relevance
“…The overall results, however, are consistent with the findings of earlier studies which have found no significant relationship between board composition and company performance (Rechner & Dalton, 1986;Fosberg, 1989;Daily & Dalton, 1993;Barnhart et al, 1994;Grace, Ireland & Dunstan, 1995;Dalton et al, 1998;Cho & Kim, 2007;Finegold et al, 2007). Despite the fact that studies by Fama and Jensen (1983), Baysinger and Butler (1985) and Baysinger and Hoskinsson (1990) have asserted that the effectiveness of a board depends on an optimal mix of executive and non-executive directors, the historical dearth of theory on the determinants of an optimal board composition (Hermalin & Weisbach, 2003) is also consonant with these findings.…”
Section: Results Of Hypothesis Testing H 1 : Board Composition (The Psupporting
confidence: 90%
“…The overall results, however, are consistent with the findings of earlier studies which have found no significant relationship between board composition and company performance (Rechner & Dalton, 1986;Fosberg, 1989;Daily & Dalton, 1993;Barnhart et al, 1994;Grace, Ireland & Dunstan, 1995;Dalton et al, 1998;Cho & Kim, 2007;Finegold et al, 2007). Despite the fact that studies by Fama and Jensen (1983), Baysinger and Butler (1985) and Baysinger and Hoskinsson (1990) have asserted that the effectiveness of a board depends on an optimal mix of executive and non-executive directors, the historical dearth of theory on the determinants of an optimal board composition (Hermalin & Weisbach, 2003) is also consonant with these findings.…”
Section: Results Of Hypothesis Testing H 1 : Board Composition (The Psupporting
confidence: 90%
“…These government pressures related to the protection of stakeholder interests have had a great impact on corporate business, so most Korean firms have implemented a short-term perspective CSR in order to defend themselves against enormous pressures [20]. This short-term perspective CSR of Korean companies has made companies focus on donations or short-term events [68]. The corporate governance structure of most Korean companies is characterized by the "owner-controlled" feature, in which the CEO is heavily influenced by major shareholders or founding owners.…”
Section: Csrmentioning
confidence: 99%
“…In family controlled firms, outside directors, particularly independent directors, may not be fully committed to their monitoring role, either due impinging authority of promoters or due to their familiarity with them (Chen and Jaggi, 2000;Leblanc and Giles, 2005). Cho and Kim (2007) suggest that the firm performance may deteriorate due to the greater power concentration in the hands of insiders due significant agency cost arising between insiders and minority shareholders. Outside directors, in such context may not act as effective monitors of management due to persistence of high information asymmetry.…”
Section: Effect Of Insider Ownership On Outsider Directors Performancmentioning
confidence: 99%